(untitled) (Indian Journal of Public Health Research & Development, 2022)
It is the era of non-communicable diseases (NCDs), non-communicable diseases are the leading global cause of death, causing more deaths than all others causes combined, and they strike hardest at the world’s low and middle income populations. This was a school based cross-sectional study carried out with the objective of finding the prevalence and awareness of risk factors for selected Non-Communicable diseases(Hypertension, IHD and diabetes) among the urban and rural government high school students, with a sample size of 510 (255 urban and 255 rural) drawn by simple random sampling method. This study was conducted using a pre-tested, semistructured questionnaire based on the study done by Diwakaran et al.,With modifications made to cater the need of the study. Awareness of Hypertension was 39.8%and 30.6% (statistically significant, p = < 0.001) among the rural and urban study subjects respectively. In our study, 20.1% of rural and 28.2% of urban children were consuming fast foods daily. 64.5% of rural and 60.8% of urban children were consuming Fruits and vegetables daily. There was significant difference in Fruits and Vegetable consumption pattern was observed between two groups. Similarly14.3% of rural and 27.1% of urban children were consuming Soft Drinks daily. 20.1% of rural and 20.8% of urban children thought that re-use of cooking oil is good for health, which was statistically not significant. Awareness of risk factors like Alcohol, Tobacco, Stress / anxiety, Obesity, passive smoking as risk factors for Hypertension, was significantly higher in rural areas than in urban areas as a risk factor for HTN. Were as in urban area Awareness of Fast food consumption, reuseof cooking oil was significantly higher in urban areas.